2017
DOI: 10.1039/c7sm00987a
|View full text |Cite
|
Sign up to set email alerts
|

3D shape evolution of microparticles and 3D enabled applications using non-uniform UV flow lithography (NUFL)

Abstract: The generation of microparticles with non-spherical morphologies has generated extensive interest because of their enhanced physical properties that can increase their performance in a wide variety of clinical and industrial applications. A flow lithographic technique based on stop flow lithography (SFL) recently showed the ability to fabricate particles with 3D shapes via manipulation of the UV intensity profile in a simple 2D microfluidic channel. Here, we further explore this flow lithographic method, calle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Magnetic nanoparticles embedded into nonplanar, bullet-shaped microneedles give access to mild invasive therapy [9].…”
Section: Patchy Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic nanoparticles embedded into nonplanar, bullet-shaped microneedles give access to mild invasive therapy [9].…”
Section: Patchy Particlesmentioning
confidence: 99%
“…The monomer solution is pumped through a microfluidic device, where photopolymerization occurs. The polymer particles (sometimes of extreme shape) are collected after having left the device [9,119] and have been used for the controlled synthesis of bullet-shaped, 12.4µm long, magnetic and non-magnetic microparticles using stop-flow lithography, which gives the possibility of executing mild invasive drug delivery via microneedles. Wu et al [96] demonstrated that in the case of monodisperse rifampicin-PLGA core-shell microcapsules, the burst-release can be decreased with increased encapsulation efficiency, and the release can be controlled by increasing the wall thickness.…”
Section: Lithographymentioning
confidence: 99%
“…Recently, a modied ow lithography technique was proposed for the synthesis of microparticles with 3D anisotropy beyond 2D extruded shapes. [147][148][149] Habasaki et al presented vertical ow lithography (VFL), an application of stereolithography concepts to conventional ow lithography, which allowed better control over the fabrication of 3D anisotropic microparticles. 150 In VFL, the light exposure and photocurable resin ow directions were aligned to enable the stacking of multiple photopolymerized layers with controlled 2D shape and thickness (Fig.…”
Section: An Optical Methods For Fabricating Complex-shaped Microparticlesmentioning
confidence: 99%
“…While flow‐lithography based particle fabrication, in which photocurable polymers are flowed through a microfluidic chip and polymerized by UV light passing through a photomask, has shown to have excellent control of particle shape along a single 2D extrusion axis, a similar level of shape control in the direction of flow is yet to be achieved . In recent years, there have been efforts to improve the complexity of particles beyond 2D extruded shapes through techniques such as hydrodynamic flow shaping and nonuniform flow lithography . However, the mechanisms enabling these methods, or inertial focusing and nonuniform UV light intensity, are not precise and are difficult to control, limiting particle shape design freedom.…”
Section: Methodsmentioning
confidence: 99%